The conservation of waterbirds and their habitat in New Zealand - Newcombe, F L (Wildfowl, 1959)
This brief account of one of New Zealand’s big wildlife problems was prepared in 1957 as a submission to the Soil Conservation and Rivers Control Council by the Department of Internal Affairs. its purpose was to introduce a subject fraught with vital consequences for waterbirds, particularly waterfowl, and the sport of game shooting in New Zealand. After being received by the Council, it was suggested that an outline of this conservation problem be prepared as a pamphlet for distribution to a wider audience. With the variety of habitats utilised by some species of birds at varying times of the year the term waterbird needs to be treated with elasticity. Waterbird here is meant to cover those species which are entirely or to a great degree dependent on areas of still fresh water whether large or small, e.g., lakes, lagoons or ponds, or whether there be free water merely interspersed amongst vegetation, e.g., swamps, or whether the ground surface is merely damp or wet.